Modulation of conformational features and oligomerization of MMACHC by cobalamin variants: impact of the R161Q mutation in cblC disease - Lisa Longo; Maria Assunta Costa; Rita Carrotta; Maria Rosalia Mangione; Vincenzo Martorana; Marco Tutone; Maria Grazia Ortore; Paula M. Garcia-Franco; Sonia Vega; Adrian Velazquez-Campoy; Rosa Passantino; Silvia Vilasi (European Biophysics Journal, 2026)
Vitamin B12 (cobalamin, Cbl) is a coordination compound of the cobalt, located at the center of a corrin ring composed of four pyrrolic-like groups. The cobalt ion can be bound to a variety of upper axial ligands, which vary among different cobalamin forms, including hydroxocobalamin (OHCbl), cyanocobalamin (CNCbl), methylcobalamin (MeCbl), and adenosylcobalamin (AdoCbl). MeCbl and AdoCbl are considered the biologically active forms, serving as cofactors in the metabolism of methylmalonic acid (MMA) and homocysteine (HCY). Impaired conversion of these metabolites leads to their pathological accumulation, resulting in severe cellular damage. This is precisely what occurs in cblC deficiency, a rare inborn disorder caused by mutations in the MMACHC protein, which plays a crucial role in binding and processing the various cobalamin forms. Mutations affecting MMACHC function impair its ability to correctly handle cobalamins, leading to the disease. In this study, we evaluated the impact of various cobalamin forms, specifically AdoCbl, MeCbl, and CNCbl, on the stability and oligomeric organization of the wild type MMACHC protein, using circular dichroism spectroscopy, native gel electrophoresis, and small-angle X-ray scattering. Moreover, isothermal titration calorimetry experiments provided insights into the thermodynamic parameters governing MMACHC binding to these cobalamins. In addition, we also assessed how the R161Q mutation in MMACHC alters the affinity of this protein for the different vitamin B12 forms, leading to decreased stability and impaired homodimerization, a process likely relevant to its functional role. Our findings provide molecular insights into cblC pathogenesis and advance our understanding of MMACHC structure–function relationships.

A new ginger extract characterization: Immunomodulatory, antioxidant effects and differential gene expression - Roberta Russo; Maria Assunta Costa; Nadia Lampiasi; Marco Chiaramonte; Alessia Provenzano; Maria Rosalia Mangione; Rosa Passantino; Francesca Zito (Food Bioscience, 2023)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.